The effect of contingencies on mutual influence among quality awards and quality initiatives. Issue 6 (10th October 2016) - Upadhyaya, Gururaj; Bhat, Subrahmanya
Abstract : Purpose: The purpose of this paper is to examine the interactive nature/mutual influence (MI) among quality initiatives (QI) and quality awards (QA) in Indian organizations subject to three contingencies, namely, QA won, QI adopted before winning a QA and QI adopted after winning a QA. Design/methodology/approach: Administration of survey to collect the data were followed by validity and reliability analyses of the instrument. Hypotheses were tested by parametric/non-parametric one-sample and independent-samples tests. Findings: The inferences on the effect of contingencies on the MI were inconclusive. Eight QI adopted before winning the QA, have influenced four such Indian QA. Three Indian QA have influenced four QI that were adopted after winning these QA. However, this MI is independent of specific QI adopted/QA won. Research limitations/implications: The approach to test the hypotheses, small sample size and generic research questions have led to "preliminary" recommendations/inferences. Further research with larger data and advanced methods for analysis of interaction is suggested. Practical implications: Based on clarity of MI, preliminary recommendations for adopting some QI before/after winning a QA were made. The way in which these recommendations can be used by experienced and fresh adopters of QI/QA and givers of QA has been outlined. Originality/value: This study attempts to fill the gap of scarce holistic studies (that evaluate numerous QI and QA models) on the interactive nature of QI and the dissemination of QI into different periods of Continuous Improvement journey.